Efeito da Somatotropina Recombinante Bovina (rBST) no Desempenho de Novilhos Alimentados com Diferentes Volumosos - Ezequiel, Jane Maria Bertocco; Sampaio, Alexandre Amstalden Moraes [UNESP]; Da Silva, Fernanda Pereira [UNESP]; Sancanari, Juliana Borsari Dourado [UNESP]; Macari, Marcos [UNESP]; De Brito, Rodolfo Marques [UNESP]; Kronka, Sérgio Nascimento [UNESP] (My University, 1999)
Effect of recombinant bovine somatotropin (rBST) on the performance of steers fed diets with different forages was evaluated. Forty crossbred steers, with average 360.2 kg LW and 30 months of age, were used. The animals were fed diets containing different forages (corn silage, sugarcane, corn silage + sugarcane and hydrolyzed sugarcane bagasse), and received an application of 320 mg rBST at every 28 days and were weighed at every 14 days during an experimental period of 84 days. The weight gain, dry matter and protein per kg of weight gain and feed:gain ratio were evaluated. There were no differences on the weight gain among the animals that received (1.210 kg/head•d) or not (1.062 kg/head·d) rBST, although the animals that received rBST had higher weight gain in the periods after the second and third hormone application. There were, also, no differences among the diets containing corn silage (1.100 kg/head•d), sugarcane (1.240 kg/head•d), corn silage + sugarcane (1.064 kg/head·d) and sugarcane bagasse (1.138 kg/ head·d). The feed:gain ratios were 9.43 and 9.69 kg MS/kg of weight gain for the animals that receiving and not receiving rBST, respectively. The crude protein intake decreased with the rBST application and was more expressive in the diet containing sugarcane. There was no interaction between the hormone application and the forage type.
Effect of Recombinant Bovine Somatotropin (rBST) on the Performance of Steers Fed Different Forages
Keywords: Beef cattle; Bovine somatotropin; Corn silage; Feedlot; Hydrolyzed bagasse; Performance; Sugarcane